Enhancing Criminology Students’ Mathematics Problem-Solving Ability Through Criminology-Based Word Problem Strategy (CBWPS) - Mosquiter-Bentoy, Joy; Evardo Jr., Orville J.; Itaas, Estela (Future Science / FSH-PH Publications, 2025)
The study aimed to enhance criminology students’ mathematics problem-solving abilities using a criminology-based word problem strategy (CBWPS) and to explore their experiences and coping mech-anisms with this approach. Employing a mixed-method explanatory sequential design, the quantitative phase utilized a quasi-experimental one-group pretest-posttest framework with 38 partici-pants, while the qualitative phase involved phenomenological in-depth interviews with 10 students. Results revealed a significant im-provement in students' problem-solving skills, with a marked in-crease in post-test scores compared to pre-test results (mean gain: 8.11, p<0.05). The intervention fostered critical thinking and en-gagement by contextualizing mathematical concepts in criminology scenarios, making learning more relevant. However, students faced challenges such as unfamiliar terminologies and difficulties with complex calculations. They coped by analyzing problems carefully and drawing motivation from their aspirations. The study recommends training mathematics educators in implementing CBWPS and inte-grating such strategies into criminology curricula to enhance analyti-cal skills and professional preparedness.